Solar cells based on copper oxide and titanium dioxide prepared by reactive direct-current magnetron sputtering - Wisz, Grzegorz; Sawicka-Chudy, Paulina; Sibiński, Maciej; Starowicz, Zbigniew; Płoch, Dariusz; Góral, Anna; Bester, Mariusz; Cholewa, Marian; Woźny, Janusz; Sosna-Głębska, Aleksandra (Opto-Electronics Review, 2021)
In this study, solar cells based on copper oxide and titanium dioxide were successfully manufactured using the reactive direct-current magnetron sputtering (DC-MS) technique with similar process parameters. TiO2/CuO, TiO2/Cu2O/CuO/Cu2O, and TiO2/Cu2O solar cells were manufactured via this process. Values of efficiencies, short-circuit current, short-circuit current density, open-circuit voltage, and maximum power of PV devices were investigated in the range of 0.02÷0.9%, 75÷350 µA, 75÷350 µA/cm2, 16÷550 mV, and 0.6÷27 µW, respectively. The authors compare solar cells reaching the best and the worst conversion efficiency results. Thus, only the two selected solar cells were fully characterized using I-V characteristics, scanning electron microscopy, X-ray diffraction, ellipsometry, Hall effect measurements, and quantum efficiency. The best conversion efficiency of a solar cell presented in this work is about three times higher in comparison with the authors’ previous PV devices.